4,6-dimethyl-2-(o-tolyliminomethyl)quinoline - Akkurt, M; Öztürk, S; Aygün, M; Aydogan, F (MUNKSGAARD INT PUBL LTD, 2001)
The molecule of the title compound, C19H18N2, is not planar. The dihedral angle between the quinoline and phenyl rings is 118.5 (1)degrees.
Keywords: Crystallography